Learning psychodynamic psychotherapy in Southeast Asia - Loo, Jiann Lin; Ang, Jin Kiat; Subhas, Natasha; Ho, Brian Kong Wai; Zakaria, Hazli; Alfonso, César A. (Guilford Publications, 2017)
The subjective nature of psychodynamic psychotherapy (PP) makes training and supervision more abstract compared to other forms of psychotherapy. The issues encountered in the learning and supervision process of PP of Malaysian psychiatry trainees are discussed in this article. Issues of preparation before starting PP, case selection, assessment of patients, dynamic formulations, supervision, anxieties in the therapy, countertransference, termination of therapy, the treatment alliance, transfer of care, the therapeutic setting, and bioethical considerations are explored. Everyone's experience of learning PP is unique and there is no algorithmic approach to its practice. With creative thinking, effort, and “good enough” supervision, a trainee can improve PP skills, even in underserved areas of the world.